Illocutionary Speech Act Analysis in the Nightbooks Movie - Hosiaa Hosiaa; Ayu Oktaviani; Yulfi Yulfi (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This research analyzes the types of illocutionary acts. Therefore, the problem of this research is "What types of illocutionary acts are found in the Nightbooks movie?. The aim of this research is to describe the types of illocutionary acts found in the Nightbooks movie. Data is analyzed through several steps including identification, analysis, classification, description and drawing conclusions. The author uses descriptive qualitative research to collect data, through several steps including watching movie, listening to speech in movie, identifying and classifying data. After investigating the types in the movie, the author found several findings. The illocutionary acts in the movie can be analyzed into several types, namely 5 commissive acts, 4 representative acts, 6 directive acts, 4 expressive acts and declarative acts. In summary, the illocutionary acts used in the movie aim to analyze the types of illocutionary acts used in the Nightbooks movie.